Blood ties : a novel - Nesbø, Jo, 1960- (Alfred A. Knopf, 2025)
"By all accounts, Carl and Roy Opgard are doing quite well for themselves. Or at least they're doing as well as can be expected in a small town like Os. Carl manages the area's swanky and successful spa and hotel, while Roy runs a nearby gas station and harbors grand plans to build it out into an entire amusement park complete with a roller coaster. But when news breaks about a new highway to be built nearby, bypassing Os and leaving the town cut-off and isolated, it's clear that something has to be done... even if the methods are bound to be dirty. Fortunately, Carl and Roy have experience with just that kind of work. Meanwhile, the town sheriff has gotten his hands on new technology that will enable him to take a deeper look at a slate of unsolved murders from years past - including that of his own father. And just as the sheriff reopens his investigation, the death toll begins to climb. It's like Roy says about his roller coaster: "Once it's rolling, it's too late to get off." Blood Ties is a tense, compulsively readable tour de force about loyalty, family ties, and love that is as destructive as it is powerful"--